Kepemimpinan Religius Bhikkhu di Sekolah Tinggi Agama Buddha - Sigit Budiyanto; Ibrahim Bafadal; Burhanuddin Burhanuddin (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This research was conducted using a qualitative approach with a multi-site study design. This research was conducted at Kertaraja Buddhist College in Batu and Smaratungga Buddhist College in Ampel. This study aims to explain (1) religious values that inspire the leadership of monks in Buddhist educational institutions, (2) the type of monk's leadership in Buddhist educational institutions, (3) the principles of monk's leadership in Buddhist education institutions. The results of this study are as follows: first, internal encouragement in the form of experience as a leader and encouragement to serve and meet academic qualifications, while external encouragement is basically appointed by the foundation to become chairman. Religious values in the leadership of monks in higher education institutions of Buddhism are values contained in the dasa raja dhamma. Second, the type of monk leadership in Buddhist religious education institutions is mixed, namely: democratic type, delegate leadership behavior and participative leadership. The way the head of higher education involves members to achieve organizational goals is by placing the right people, giving the vice chairman a big role and active participation of members. A personal figure as a monk who is a Buddhist clergyman and uses a humanistic approach, as well as an element of kinship in work culture. Third, the use of communication tools by the Head of the Buddhist College when not in place. Abstrak: Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif dengan rancangan studi multi situs. Penelitian ini dilakukan di STAB Kertaraja Batu dan STIAB Smaratungga Ampel. Penelitian ini bertujuan menjelaskan (1) nilai religius yang menjiwai kepemimpinan bhikkhu di lembaga pendidikan agama Buddha, (2) jenis kepemimpinan bhikkhu di lembaga pendidikan agama Buddha, (3) prinsip kepemimpinan bhikkhu di lembaga pendidikan agama Buddha. Hasil penelitian ini adalah sebagai berikut. Pertama, yaitu dorongan internal berupa pengalaman sebagai pemimpin dan dorongan untuk mengabdi dan memenuhi syarat kualifikasi akademik, sedangkan dorongan eksternal yaitu pada dasarnya ditunjuk oleh yayasan untuk menjadi ketua. Nilai religius dalam kepemimpinan bhikkhu di lembaga pendidikan tinggi agama Buddha yaitu nilai yang termuat dalam dasa raja dhamma. Kedua, jenis kepemimpinan bhikkhu di lembaga pendidikan agama Buddha mix (campuran), yaitu tipe demokratis, perilaku kepemimpinan delegasi dan partisipatif. Cara ketua perguruan tinggi dalam melibatkan anggota untuk mencapai tujuan organisasi yaitu dengan melakukan penempatan orang yang tepat, memberikan peran besar wakil ketua dan partisipasi aktif anggota. Sosok personal sebagai bhikkhu yang merupakan rohaniawan buddhis dan menggunakan pendekatan humanistik, serta unsur kekeluargaan dalam budaya kerja. Ketiga, penggunaan alat komunikasi oleh Ketua Sekolah Tinggi Agama Buddha ketika tidak berada di tempat.